2012
DOI: 10.1038/hdy.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

The maternal cytoplasmic environment may be involved in the viability selection of gametes and zygotes

Abstract: Segregation distortion is the phenomenon whereby the observed genotypic frequencies of a locus fall outside the expected Mendelian segregation ratio, and it is increasingly recognised as a potentially powerful evolutionary force. The main reason for segregation distortion is a difference in the viability of gametes and zygotes caused by viability loci in the segregating progeny. However, the maternal cytoplasm may also be involved in the viability selection of gametes and zygotes. The objectives of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The other SDL likely reflected zygotic selection. These results provided a better understanding of the putative mechanism of SD, which has been reported in many plant species (Anhalt et al, 2008; Fishman et al, 2008; Cai et al, 2011; Castro et al, 2011; Diouf and Mergeai, 2012; Tang et al, 2013). …”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…The other SDL likely reflected zygotic selection. These results provided a better understanding of the putative mechanism of SD, which has been reported in many plant species (Anhalt et al, 2008; Fishman et al, 2008; Cai et al, 2011; Castro et al, 2011; Diouf and Mergeai, 2012; Tang et al, 2013). …”
Section: Discussionsupporting
confidence: 62%
“…Tang et al (2013) showed that the maternal cytoplasmic environment might be involved in the viability selection of gametes and zygotes resulting from dramatic changes in the genotypic frequencies of the SDL in the two reciprocal cross populations. In the present study, six out of eleven SDL on chromosome 18 were dependent on the cytoplasmic environment, but other SDL were not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study (Tang et al, 2013a), several segregation distortion loci (SDL) were identified in two cytoplasm background PROC QTL procedures proposed by Hu and Xu (2009). In our previous study (Tang et al, 2013a), several segregation distortion loci (SDL) were identified in two cytoplasm background PROC QTL procedures proposed by Hu and Xu (2009).…”
Section: Discussionmentioning
confidence: 91%